The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1186/cc6797
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and costs of blunt trauma in England and Wales

Abstract: Background Trauma represents an important public health concern in the United Kingdom, yet the acute costs of blunt trauma injury have not been documented and analysed in detail. Knowledge of the overall costs of trauma care, and the drivers of these costs, is a prerequisite for a cost-conscious approach to improvement in standards of trauma care, including evaluation of the cost-effectiveness of new healthcare technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 8 publications
7
39
0
4
Order By: Relevance
“…Over 90% of injuries were alleged assaults. The median (interquartile range [IQR]) GCS was 15 across the whole sample, falling to 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) in the ISS 35-75 group. Mean (95% confidence interval [CI]) systolic blood pressure in A&E was 124 mmHg (122-126) and mean pulse rate was 94 beats per minute (92-95).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Over 90% of injuries were alleged assaults. The median (interquartile range [IQR]) GCS was 15 across the whole sample, falling to 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) in the ISS 35-75 group. Mean (95% confidence interval [CI]) systolic blood pressure in A&E was 124 mmHg (122-126) and mean pulse rate was 94 beats per minute (92-95).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…The median total hospital length of stay was 9 days, and 69% of patients underwent at least one surgical procedure. 10 In study by Youssef Saleh et al the mean hospital stay was 19.42 days in 60% of the cases and 34 days in rest 40% of the patients. 4 …”
Section: Resultsmentioning
confidence: 93%
“…In a systematic review of costutilization studies in trauma (adult and pediatric), Willenberg and colleagues 15 reported a median per-patient cost of $22 448 for the treatment of acute trauma. Despite the variability among the studies included in the review, the presence and type of surgery 16,17 and higher ISS 7 independently predicted increased cost. The higher hospitalization costs observed in our study, therefore, are not surprising, given that we focused on surgical trauma patients, who had higher ISS than their nonsurgical counterparts.…”
Section: Discussionmentioning
confidence: 99%